An Analysis of the Syro-Hexapla of Job and Its Relationship to Other Ancient Sources - Meade, John Daniel (Aramaic studies, 2016)
The Syro-Hexapla is a valuable witness to the text of Origen’s Hexapla. This article describes the marginal material in the Syro-Hexapla of Job under the following headings: (1) hexaplaric notes, (2) longer scholia (from patristic works), (3) textual variants and other versions, (4) Greek words, and (5) exegetical notes / glosses. By examining all of the materials within the manuscript more insight into its history and provenance was made possible. According to the evidence, Syro-Hexapla Job probably originated in or around Alexandria and was probably translated from the Tetrapla or a text that preserved four Greek versions of Job along with other marginal material.